Study on the Marketing Strategy of "7 Days lnn" Based on the New Media Perspective. Issue 4 (February 2021) - Su, Lanlan; Fang, Shihao; Lai, Fan; Cheng, Congxi; Duan, Xiangyu
Abstract: With the vigorous development of domestic economy and tourism industry & the increasing popularity of mobile Internet technology in hotel industry, the development speed of economical chain hotels is also greatly improved, and the market competition is becoming more and more fierce. As the representative of economical chain hotels, 7 Days lnn is facing severe challenges, but it is also full of unlimited development opportunities. Based on the investigation of the new media marketing of 7 Days lnn, this paper has analyzed the problems existing in the new media marketing of 7 Days lnn, and finally put forward the corresponding countermeasures.